How Market Research Shapes Market Spatiality: A Global Governmentality Perspective - Bjerrisgaard, Sofie Møller; Kjeldgaard, Dannie (Journal of macromarketing, 2013)
This article focuses on how various ideological representations of the market—most notably the myth of the global market—produce certain effects on the way in which market spaces materialize and simultaneously draw the contours of ideal organizational and consumer subjectivities. We employ a governmentality perspective to address global myth market creation and hence the emergence of “glocal” market spaces. That is, the article explores how representations of glocal markets create specific interventions in the form of marketing tactics that subsequently have performative consequences for interorganizational and intraorganizational as well as consumer subject positions.